Feasibility study of temporary permanent pacemaker in patients with conduction block after TAVR - Chang, Sanshuai; Liu, Xinmin; Lu, Zhi-Nan; Yao, Jing; Yin, Chengqian; Wu, Wenhui; Yuan, Fei; Luo, Taiyang; Liu, Ran; Yan, Yunfeng; Zhang, Qian; Pu, Junzhou; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Limited data exist on the use of temporary permanent pacemaker (TPPM) to reduce unnecessary PPM in patients with high-degree AVB (HAVB) after transcatheter aortic valve replacement (TAVR). Objectives: This study aims to determine the feasibility of TPPM in patients with HAVB after TAVR to provide prolonged pacing as a bridge. Methods: One hundred and eleven consecutive patients undergoing TAVR were screened from August 2021 to June 2022. Patients with high-degree AVB (HAVB) eligible for PPM were included. TPPM were used in these patients instead of conventional temporary pacing or early PPM. Patients were followed up for 1 month. Holter and pacemaker interrogation were used to determine whether to implant PPM. Results: Twenty one patients met the inclusion criteria for TPPM, of which 14 patients were third-degree AVB, 1 patient was second-degree AVB, 6 patients were first degree AVB with PR interval＞240ms and LBBB with QRS duration＞150ms. TPPM were placed on the 21 patients for 35±7 days. Among 15 patients with HAVB, 26.7% of them (n=4) recovered to sinus rhythm; 46.7% (n=7) recovered to sinus rhythm with bundle branch block. The remains of 26.7% patients (n=4) still had third-degree AVB and received PPM. For patients with first-degree AVB and LBBB, PR interval shortened to < 200ms in all 6 patients and LBBB recovered in 2 patients. TPPM were successfully removed from all patients and no procedure-related adverse events occurred. Conclusions: TPPM is reliable and safe in the small sample of patients with conduction block after TAVR to provide certain buffer time to distinguish whether a PPM is necessary. Future studies with larger sample are needed for further validation of the current results.